Single‐cell transcriptomics reveals distinct inflammation‐induced microglia signatures. (11th September 2018) - Sousa, Carole; Golebiewska, Anna; Poovathingal, Suresh K; Kaoma, Tony; Pires‐Afonso, Yolanda; Martina, Silvia; Coowar, Djalil; Azuaje, Francisco; Skupin, Alexander; Balling, Rudi; Biber, Knut; Niclou, Simone P; et al.
Abstract: Microglia are specialized parenchymal‐resident phagocytes of the central nervous system (CNS) that actively support, defend and modulate the neural environment. Dysfunctional microglial responses are thought to worsen CNS diseases; nevertheless, their impact during neuroinflammatory processes remains largely obscure. Here, using a combination of single‐cell RNA sequencing and multicolour flow cytometry, we comprehensively profile microglia in the brain of lipopolysaccharide (LPS)‐injected mice. By excluding the contribution of other immune CNS‐resident and peripheral cells, we show that microglia isolated from LPS‐injected mice display a global downregulation of their homeostatic signature together with an upregulation of inflammatory genes. Notably, we identify distinct microglial activated profiles under inflammatory conditions, which greatly differ from neurodegenerative disease‐associated profiles. These results provide insights into microglial heterogeneity and establish a resource for the identification of specific phenotypes in CNS disorders, such as neuroinflammatory and neurodegenerative diseases. Synopsis: Using single‐cell transcriptomics and multicolour flow cytometry this study presents comprehensive profiles of microglia in LPS‐injected mice, providing insight into microglia heterogeneity, and establishing a resource for the identification of specific phenotypes in CNS disorders. Microglia homeostatic signatures are mainly lost upon acute systemic inflammation. Inflammation‐induced microglia segregate into two distinct reactive states. Inflammation‐induced microglia signatures are distinct from neurodegenerative disease‐associated profiles. Abstract : Using single‐cell transcriptomics and multicolour flow cytometry this study presents comprehensive profiles of microglia in LPS‐injected mice, providing insight into microglia heterogeneity, and establishing a resource for the identification of specific phenotypes in CNS disorders.